2015
DOI: 10.4103/1735-1995.168403
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the association of serum selenium and metabolic syndrome

Abstract: Background:This systematic review paper aims to study the experimental and human studies on the relationship between metabolic syndrome (MetS), its component and selenium (Se) concentration.Materials and Methods:The literature was searched in PubMed, Scopus, and Google Scholar databases with no time limitation using MetS X and Se key words in medical subject heading. The related papers were selected in three phases. After quality assessment, two reviewers extracted the data, whereas the third reviewer checked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Moreover, selenium blood levels are related to a decrease in ROS production; consequently, selenium seems to have a protective role against oxidative stress-associated disorders, including cardiovascular disease [21,22]. In the present systematic review, only one study with selenium was available [44].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, selenium blood levels are related to a decrease in ROS production; consequently, selenium seems to have a protective role against oxidative stress-associated disorders, including cardiovascular disease [21,22]. In the present systematic review, only one study with selenium was available [44].…”
Section: Discussionmentioning
confidence: 97%
“…Research has associated chromium, vanadium, and zinc with insulin action and glucose metabolism [17][18][19][20]; chromium, silicon, zinc, and copper with angiogenesis and vascular biology [13]; and zinc and selenium with oxidative stress and cardiovascular diseases [20][21][22]. Trace elements, such as copper, zinc, and iron, are involved in cytokine production, inflammation, and immune defense [15,23], and copper acts as enzyme cofactors or regulators of transcription factors [24].…”
Section: Introductionmentioning
confidence: 98%
“…Although obesity is commonly associated with many cardiometabolic diseases like hypertension and diabetes (Odu-wole et al, 2012), research has reported localized adipose tissue or its distribution, particularly an android fat pattern with excessive fat around the abdomen to be more closely associated with these diseases than obesity itself (Ben Mohammed et al, 2011;Buchan et al, 2013). These findings have renewed the scientific community's interest in studying body fat distribution and its relative effect on health, especially among the youth (Lee & Arslanian, 2007;Kelishadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The waist circumference (WC), a proxy measure of abdominal fat distribution (Maffies, 2000) is a component of metabolic syndrome, the coexistence of many cardiovascular disease risk factors in an individual which is linked to type 2 diabetes mellitus, coronary heart disease, and some types of cancer (Kelishadi et al, 2015). Although abdominal fat is considered a chronic disease risk, visceral adipose tissue (VAT) (intrabdominal fat depot) is strongly associated with metabolic abnormalities than subcutaneous adipose tissue (SAT) (present under the skin and abdominal area) Ibrahim, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Healthy changes in lifestyle and diet (as using functional foods and bioactive nutrients) are recommended as strategies to combat MetS. [ 10 11 ]…”
Section: Introductionmentioning
confidence: 99%